2011
DOI: 10.1021/nn103473s
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Liquid Hg/Solid β-HgS Metal−Semiconductor Heterostructures with Unique Electrical Properties

Abstract: Liquid metal-solid semiconductor heterostructures, Hg heads combined with single-crystalline β-HgS tails, with controllable sizes and well-defined interfaces have been fabricated for the first time via one-pot synthesis. Such heterostructures can exist in water with good stability due to coordination adsorption of cysteine molecules onto the surface of both Hg and HgS through Hg-S bonds. Two-probe current-voltage curve measurements reveal that good ohmic contacts without additional resistance contacts are gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…[34] I D /I G ratios which gives quantification of surface defects, are calculated for graphene, MnS/G (40 %), MnS/G (50 %) and MnS/G (60 %), and the values are 1.14, 1.23, 1.33, and 1.48, respectively. [37] These clusters decompose under pressurized condition to form sub-micron to micro-sized MnS structures. Figure 3a-c show FE-SEM images of MnS/G (40 %), MnS/G (50 %) and MnS/G (60 %) hybrid catalysts, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] I D /I G ratios which gives quantification of surface defects, are calculated for graphene, MnS/G (40 %), MnS/G (50 %) and MnS/G (60 %), and the values are 1.14, 1.23, 1.33, and 1.48, respectively. [37] These clusters decompose under pressurized condition to form sub-micron to micro-sized MnS structures. Figure 3a-c show FE-SEM images of MnS/G (40 %), MnS/G (50 %) and MnS/G (60 %) hybrid catalysts, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…L-cysteine is a well-known amino acid with more number of active functional groups such as -NH 2 , -COOH and -SH and they have a strong tendency to coordinate with inorganic cations like Mn 2 + to form metal-ligand clusters. [37] These clusters decompose under pressurized condition to form sub-micron to micro-sized MnS structures. In order to visualize MnS particle distribution on to graphene support, low magnification FE-SEM images have acquired and shown in Figure S1 (See supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, prior to the solvothermal process, Ag(I) reacts easily with thiolate anion or NH 2 -groups of SCAs [43], which effectively controls the Ag + concentration by forming the Ag(I)-thiolate (or -NH 2 -) complex. Wu et al [44] reported the synthesis of smallsized Hg and HgS by formation of Hg(II)-thiolate complex, by controlling Hg 2+ concentration in the solution. Thus, we suppose that the small-sized Ag or Ag 2 S have a similar formation process.…”
Section: Analysis Of Synthetic Mechanismmentioning
confidence: 99%
“…In the past decade, semiconductor quantum dots (QDs) have become well‐established photoluminescent platforms for many scientific and industrial applications 1–3. For example, QDs are highly sensitive to charge/energy transfer, which can alter their optical properties, thus generating interest in charge/energy‐transfer‐based bio‐sensing 1, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescence across the visible spectral region with mercury chalcogenide is extremely difficult, while it is common for zinc‐ and cadmium‐based chalcogenides. Despite the potential toxicity of mercury and the restricted application in biology, it would be of great interest to develop mercury chalcogenide QDs with tunable luminescence as there is immense potentiality in their application in chemical sensing, infrared detection, and in the development of electrical devices 2, 5, 6…”
Section: Introductionmentioning
confidence: 99%